Petrographic Study of The Jampang Formation Rock Unit, Cibenda Area, Ciemas District, Sukabumi Regency, Indonesia - Dian Rahma Yoni; Afrilita; Nazla Syafitri Rangkuti; Dimas Putra Yodira (Engineering Faculty, UNSOED, 2025)
The Cibenda area, located in Ciemas District, Sukabumi Regency, is part of the Ciletuh Geopark, which has important geological diversity that requires detailed study. This study aims to determine the petrographic characteristics of the main rock units and to compile an interpretation of geological evolution based on microscopic data. The method used is thin section analysis of rock samples taken from the field and observed using a polarizing microscope. There are three main rock units studied, namely the Sandstone Unit, the Breccia Unit, and the Andesite Unit. The analysis results show that the sandstone unit consists of fine- to medium-grained rocks dominated by rock fragments and feldspar, the breccia unit is composed of polymictic components in the form of crystal tuff and sandstone in a sandstone matrix, while the andesite unit shows a porphyritic texture with plagioclase and pyroxene phenocrysts. The results of this study indicate that the depositional process and magmatic intrusion occurred gradually, forming a geological sequence that reflects the evolution from a marine environment to tectonic and magmatic activity in the Cibenda area.